Implementation of K-Means Clustering Method in Grouping Best-Selling Building Materials at Sinar Harapan Building Shop - Fadila, Aldevia; Sonita, Anisya; Witriyono, Harry; Rifqo, Muhammad Husni (Multidisciplinary Journals, 2024)
Building materials are all materials both as basic and auxiliary materials needed to build a certain building that are easily available in building stores, one of which is at the Sinar Harapan Building Shop. The purpose of this research is to build a system that can provide information on building materials that are in demand and not in demand by applying the k-means clustering method to help facilitate the management of building material sales. The results of this study have created a system for classifying in-selling and out-of-selling building materials based on the results of calculations using the k-means clustering method by testing 10 samples of building materials which get the results of 3 in-selling building materials and 7 building materials not in demand or less in demand.